Identification and analysis of ticks on Brahman and Friesian-sahiwal cattle in an institutional teaching farm in Bintulu, Sarawak, Malaysia - Idris, Nur Haziqah; Khalex, Abang Mohd Harizt; Mohammed, Muhamad Azmi; Malahubban, Masnindah; Hassan, Mohd Nasir; Mustafa, Suhaili; Paul, Bura Thlama; Syed-Hussain, Sharifah Salmah; Sadiq, Mohammed Babatunde; Altwaim, Sarah A.; Kamaludeen, Juriah (Universiti Kebangsaan Malaysia Press, 2023)
Ticks (Acari: Ixodidae) are highly prevalent in cattle raised in the tropics. The study aims to identify and determine the prevalence of tick infestation and associated factors in cattle from an institutional teaching farm in Bintulu, Sarawak, Malaysia. Physical examination was conducted on 84 cattle from the teaching farm and recovered ticks were identified. Factors such as breed, sex, age, and bodyweight of the cattle were recorded. The prevalence of tick infestation was 62.4, with a total of 229 ticks isolated from 56 cattle. The tick species were identified as Rhipicephalus microplus. Most of the recovered ticks (60.3) were from the ear, followed by the pin (13.5) and elbow (6.6). Friesian-Sahiwal breed had a higher infestation rate (26.3; P